Quantification of animal species using quantitative real-time PCR (qPCR) to verify fraud in meat products (Research, Society and Development, 2023)
Food labeling is fundamental to avoid eating a specific kind of meat for religious and cultural reasons, but mainly to avoid fraud with the purpose of obtaining financial advantages. The real-time qPCR method is commonly used to quantify DNA in a given sample by relative quantification (concentration of specific target DNA over concentration of endogenous DNA). In studies that use qPCR to quantify contaminating species, normalization is performed using a single-copy reference gene, such as myostatin, present in most mammals and birds. This study aimed to standardize the real-time qPCR technique to obtain relative quantitative results in rigged beef. For method standardization, the limit of detection (LD) resulted in a Cq fluorescence signal of 36.80 cycles in at least 9 out of 10 repetitions (90%) at a concentration of 0.008% in horse and Cq of 36.60 cycles in at least 7 of 10 repetitions (70%) at a concentration of 0.0005% in chicken. The lowest concentration at which the relative standard deviation (RSD) was ≤25% was between 0.125% and 0.031% for both horse and chicken. Even using standard quantitation curves containing 50% meat blends or 100% pure target meat, curve slope, amplification efficiency, and linear correlation were within recommended acceptance criteria. The test is sensitive and an alternative in the routine inspection of products for both human and animal consumption.